Looking for Asian butch-dykes: Exploring filmic representations of east Asian butch-dykes in Donna Lee's Enter the mullet - Lin, Hui-Ling (Journal of Lesbian Studies, 2009)
Asian butch-dykes have been overlooked in analyses of Chinese cinema, studies that often concentrate on “feminized” transgender roles. This article examines cinematic representations of Asian butch-dykes through film analysis of Enter the Mullet (2004), a five minute short, and in-depth interviews with the filmmaker, Donna Lee, a Chinese-Canadian in Vancouver. Lee’s film is inspired by Enter the Dragon (1973), starring Bruce Lee, the most recognized icon of Asian masculinity. Combining with the mullet hairstyle, which is often associated with White working-class, the filmmaker introduces viewers to the hybrid masculinity of Asian butch-dykes. The article argues that Asian female masculinity can be a strategic means of destabilizing the hegemony of White–male–middle-class masculinity
Keywords: amériques; approches et analyses; asie; canada; chine; identités LGBTQIA2+; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions